The Relationship Between Knowledge About Gingivitis in Pregnant Women and Gingivitis - Niken Arlintya Ramadhani; Imam Sarwo Edi; Bambang Hadi Sugito (Media Informasi, 2025)
Pregnancy is still lacking in oral and dental health, one of which is the problem of gingivitis. In Indonesia, 74% of pregnant women experience gingivitis, according to Riskesdas 2018. At the Bulak Banteng Health Center, Surabaya, the purpose of this study was to determine the relationship between gingivitis and pregnant women's awareness of the condition. Research methods: This study is analytical and cross-sectional. The target of the study was pregnant women. A total of thirty pregnant women. Information questionnaires and gingival index were distributed as part of the data collection process. Spearman's rho is a data analysis method used. As per the findings, pregnant women's gingival index fell under the moderate range, and their knowledge on gingivitis fell into the poor group. There was no correlation between pregnant women's knowledge of gingivitis and their gingivitis, according to the study's findings. Conclusion: According to the analysis's findings, there was no correlation between pregnant women's knowledge of gingivitis and the condition during 2025 at the Bulak Banteng Health Center Dental Clinic in Surabaya.